Transvaginal Sacrospinous Ligament Fixation for Pelvic Organ Prolapse Stage III and Stage IV Uterovaginal and Vault Prolapse - Pratiksha Gupta (Iranian Journal of Medical Sciences, 2015)
The result of transvaginal sacrospinous ligament fixation technique, as part of the vaginal repair procedure for massive uterovaginal (Pelvic Organ Prolapse stage III and stage IV and vault prolapse) is evaluated. A total of 32 women were included in the present case series. Marked uterovaginal prolapse was present in 28 women and four had vault prolapse following hysterectomy. Patients with vault prolapse and marked uterovaginal prolapse underwent sacrospinous colpopexy. The mean follow-up period was 2.5 years. Out of the 28 patients with previous marked uterovaginal prolapse, only one had small cystocele 3 years after the surgery. This patient was asymptomatic and did not require repeat surgery. One woman had post-operative urinary tract infection and two had buttock discomfort, one had ischiorectal abscess and two had cuff cellulitis. All complications were dealt with successfully. No other major intra- and post-operative complications occurred. Transvaginal sacrospinous colpopexy can be performed together with vaginal hysterectomy, with marked uterovaginal prolapse and vault prolapse.